2012
DOI: 10.1111/1477-9552.12001
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Valuation of Environmentally Friendly Production Practices in Wines, considering Asymmetric Information and Sensory Effects

Abstract: Agricultural producers and food marketers are increasingly responding to environmentally friendly cues from consumers, even though privately appropriated values associated with a range of food products commonly rank above their public‐good counterparts. Wine can be considered an ideal product to examine these issues given consumers’ highly subjective sensory preferences towards wine, and a winegrape production process that is relatively intensive in the use of chemical inputs for the control of disease and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 30 publications
(49 reference statements)
5
61
1
Order By: Relevance
“…Over time, this will however depend on consumers making repeat purchases and that sufficient premiums are maintained. In keeping with Schmit et al (2012) it seems reasonable to assume that consumers' sensory evaluation of the products will be important implying that those pursuing a line-caught differentiation strategy should certainly strive to ensure the high quality of the product as documented by Rotabakk et al (2011). That the market seems to prefer line-caught cod and haddock of high quality should also be of interest for governments striving to optimise the value of its fish stocks.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, this will however depend on consumers making repeat purchases and that sufficient premiums are maintained. In keeping with Schmit et al (2012) it seems reasonable to assume that consumers' sensory evaluation of the products will be important implying that those pursuing a line-caught differentiation strategy should certainly strive to ensure the high quality of the product as documented by Rotabakk et al (2011). That the market seems to prefer line-caught cod and haddock of high quality should also be of interest for governments striving to optimise the value of its fish stocks.…”
Section: Discussionmentioning
confidence: 99%
“…It considers that no additives have been used in the winemaking process and also the reduction of agrochemical use, pesticide and fertilizer, particularly nitrogenous fertilizers, in the vineyard [18,50,51]. Also, traceability among all the stages has to be assured, and good sensory expectations of the product need to be satisfied if the wine is to be perceived as sustainable [23,52]. In a study Forbes et al [6] revealed that New Zealand consumers think that sustainable practices would improve the quality of the wine.…”
Section: Four Environmental Constructsmentioning
confidence: 99%
“…Although age is a control variable generally used in the consumer behavior studies [52,59], we decided not to include it because we are already analyzing two sub-samples characterized by different ages: millennials (18-35 years) and non-millennials (36-88 years).…”
Section: Control Variablesmentioning
confidence: 99%
“…31,[40][41][42][43][44][45][46][47] While some studies analyzed consumers' preferences toward environmentally friendly wine products, considering carbon neutral, organic and further eco-friendly claims, only a few of them describe in detail consumers' preferences toward biodynamic wine. 2,7,[48][49][50][51][52][53][54] Furthermore, although results from a number of studies reveal that most consumers are willing to pay a higher price for sustainable wines and a few estimated that environmentally friendly ones receive a very limited premium compared to conventional wines, to our best knowledge none describe the willingness to pay for biodynamic wines.…”
Section: Consumer Preferences and Perception Toward Biodynamic Winementioning
confidence: 99%